2017
DOI: 10.1016/j.chest.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Digital Morphometrics

Abstract: Measures of tongue size, airway visibility, and Mallampati scores were associated with increased OSA risk and severity. This study shows that digital morphometrics is an accurate, high-throughput, and noninvasive technique to identify anatomic OSA risk factors. Morphometrics may also provide a more reproducible and standardized measurement of the Mallampati score. Digital morphometrics represent an efficient and cost-effective method of examining intraoral crowding and tongue size when examining large populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…A significant correlation between the oropharyngeal soft tissue (Mallampati test and tonsillar enlargement, etc) and AHI was reported. 20 21 However, the Mallampati test was not a Open access significant parameter in our study. It is possible that the association between soft tissue and OSA is weak in Asian populations.…”
Section: Discussioncontrasting
confidence: 58%
“…A significant correlation between the oropharyngeal soft tissue (Mallampati test and tonsillar enlargement, etc) and AHI was reported. 20 21 However, the Mallampati test was not a Open access significant parameter in our study. It is possible that the association between soft tissue and OSA is weak in Asian populations.…”
Section: Discussioncontrasting
confidence: 58%
“…Tongue size was larger in the patients with OSA than in the controls in unadjusted models controlled for age, sex, and race, but the difference was not significant when the models were controlled for BMI. 23 , 24 Weight loss leads to a reduction in tongue fat content and pharyngeal length, reinforcing the association between obesity and increased tongue volume through fat infiltration. 7 …”
Section: Discussionmentioning
confidence: 91%
“…Studies using CT and magnetic resonance imaging have shown that tongue fat infiltration and upper airway soft tissue volume are associated with obesity. 6 Schwab et al 23 analyzed digital photographs of 318 controls and 542 patients with OSA. Tongue size was larger in the patients with OSA than in the controls in unadjusted models controlled for age, sex, and race, but the difference was not significant when the models were controlled for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Otolaryngologists evaluated the scale of adenoid, tonsils, tongue, and oropharynx (see Supplemental Material). [16][17][18] Obstructive Sleep Apnea Questionnaire-18 (OSA-18)…”
Section: Physical Examinationmentioning
confidence: 99%